Systematic Literature Review: Pendidikan Pancasila Dalam Membentuk Karakter Peserta Didik - Mizhar, Didi (Yayasan Sembilan Pemuda Indonesia, 2025)
This article provides an understanding to students about the important role of Pancasila Education in shaping the character of elementary school students who are smart, creative, and noble. The problem that occurs at this time is the lack of understanding of right and wrong behavior and the lack of direction from the school regarding character education. This research uses Systematic Literature Review. This research focuses on using clear and defined scientific methods to identify, select, evaluate, and summarize the results of relevant studies. Therefore, Pancasila has an important role in shaping the character of students in elementary schools, so it is necessary to instill Pancasila values to students through education. Character education through Pancasila needs to be implemented in schools in order to improve the quality of Indonesia's young generation in the future. Therefore, it is expected that Pancasila Education can shape the character of students in accordance with the values of Pancasila.